Integrating Europe's Financial Markets. - Decressin, Jörg (International Monetary Fund, 2007)
By and large, EU financial integration has been a success story. Still, the reform agenda is far from finished. What are the remaining challenges? What are the gains of closer financial market integration? This IMF book tracks the European Union's journey along the path to a single financial market and identifies the challenges and priorities that remain ahead. It pays particular attention to the most recent integration efforts in the European Union following the introduction of the euro. The study looks at the importance of financial integration, in particular for economic growth, the interpl.